Changes in retention characteristics of 9historical artificial water reservoirs near BanskáŠtiavnica, Slovakia - Kubinský Daniel; Weis Karol; Fuska Jakub; Lehotský Milan; Petrovič František (Open Geosciences, 2015)
The article is focused on the evaluation of accumulationvolume changes in 9 water reservoirs nearBanská Štiavnica (Slovakia) by comparing historical mapsand using modern bathymetric surveying technologies.The mining region of Banská Štiavnica has been inscribedinto the UNESCO List of the World and Cultural Heritagein 1993. Accumulation and transfer of sediments dependmainly on changes of land cover in the watersheds thatlead to the loss of retention capacity and reduction oflife span of reservoirs. The results of a comparison oftwo 3D models, one created from historic documentationand the other created from data of field surveying haveshown overall reduction in the volume of water totalling446484m3, i.e. 16.70%from past to current time. Causes ofsedimentation were searched in watersheds changes overtime. These were identified by comparison of historicalaerial imagery (1949) with existing aerial photographs.